EL ENGAÑO EN LA NOVELA GIREGA ANTIGUA. ALGUNAS CONSIDERACIONES (I) - Brioso Sánchez, Máximo (Myrtia, 1999)
The deceit-motiv in ancient Greek novel. Some considerations (I). In this first paper of a series general aspects of the deceit-motiv in ancient Greek novel and its precedents are studied. Some learned critic opinions are also discussed.